Influence of Al Addition Strategy on the Microstructure of a Low‐Cr Oxide Dispersion‐Strengthened Ferritic Steel. Issue 4 (12th December 2019) - Xu, Shuai; Zhou, Zhangjian; Long, Fei; Jia, Haodong; Guo, Ning; Sun, Yongduo; Yao, Zhongwen; Daymond, Mark R.
Abstract : Herein, two kinds of Fe–9Cr–8Al oxide dispersion‐strengthened (ODS) steels (prealloyed and postalloyed) are fabricated via mechanical alloying (MA), hot isostatic pressing (HIP), and subsequent hot forging. Microstructures of the milled powder and forged bulk materials are carefully characterized. The results show that the adding sequence of Al has a significant impact on the microstructure. For the postalloyed sample (adding Al during ball milling), a dual‐phase structure composed of reticular Al‐rich regions and a steel matrix is formed in the milled powder due to the highly mismatched deformability between the Al powder and the Fe–9Cr powder during ball milling. For the prealloyed sample (adding Al prior to ball milling), Al is solid solutionized into the steel matrix before ball milling, and there is no dual‐phase structure in the milled powder. In the final bulk materials, the average grain size of the prealloyed sample is much larger than that of the postalloyed sample. Moreover, the matrix of the postalloyed sample has a bimodal grain structure consisting of coarse grains closely surrounded by fine grains, whereas the prealloyed sample has a relatively uniform distribution of coarse grains. The coarsening mechanisms of Al addition on the microstructure are also discussed. Abstract : Two different Al addition methods affect the microstructures of low‐Cr oxide dispersion‐strengthened (ODS) steels at each preparation process. For the postalloying method, the dual‐phase structured ball‐milled powder leads to the bimodal grains of the steel matrix, whereas for the prealloying method, uniform distribution of Al element in the milled powder results in the uniform coarsening of the steel matrix.